Nonlinear Partial Differential Equations: Exact Solutions, Symmetries, Methods, and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains the 19 articles accepted and published in the Special Issue “Nonlinear Partial Differential Equations: Exact Solutions, Symmetries, Methods and Applications, 2023” of the MDPI “Mathematics” journal. This publication covers a wide range of topics pertaining to the theory and applications of Nonlinear Partial Differential Equations and its generalizations. These journal covers special methods for constructing solutions to nonlinear nonintegrable partial differential equations and application of differential equations to describe physical, technological and environmental processes, among other topics. The main focus of this Special Issue is the use of computer mathematics methods to obtain the results of the presented works. We hope that the reprint will be an interesting and useful resource for those working in the area of Nonlinear Partial Differential Equations: Exact Solutions, Symmetries, Methods and Applications, as well as those with the proper mathematical background and willingness to familiarize themselves with recent advances in nonlinear mathematical models. Nowadays, these influence almost all aspects of human life.